Retiform and epithelioid hemangioendothelioma arising from the spleen - Chuang-Wei Chen; Koung-Hung Hsiao; Tzung-Ju Lu; Chieh-Wen Lai (Formosan Journal of Surgery, 2019)
Splenic hemangioendothelioma (HE) is an extremely rare vascular tumor with an uncertain malignant potential. Experience of treatment with this tumor is limited due to their rare occurrence. We herein describe a case of a 53-year-old woman who was found a splenic tumor incidentally. Radiological findings revealed marked splenomegaly with multiple ill-defined hypodense masses as well as a low-density nodule at the left lobe of the liver. The patient underwent splenectomy and wedge resection of the liver. Final pathology confirmed the diagnosis of an admixture of retiform and epithelioid HE of the spleen with metastasis of the liver. However, distant metastases of bilateral lungs developed 6 months after the operation. She received oral thalidomide therapy without significant progression of the disease over a period of 26 months' follow-up. To the best of our knowledge, only 11 cases had been described in the literature. We report the first case of splenic HE metastatic to both liver and lungs. Our patient received thalidomide, a drug with antiangiogenic action, was shown to let the disease progression slow down. It may be recommended for those patients with relapsed disease or metastases.